2021
DOI: 10.1016/j.nicl.2021.102654
|View full text |Cite
|
Sign up to set email alerts
|

A neural noise account of Gilles de la Tourette syndrome

Abstract: Highlights A neural noise account on Tourette syndrome is conceptualized. We outline how neurophysiological methods can be used to test this account. The neural noise account may lead to novel treatment options.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(31 citation statements)
references
References 112 publications
0
31
0
Order By: Relevance
“…Due to its particularly notable motor symptoms, GTS has long been viewed and classified as a movement disorder, and treatment efficacy is indeed usually evaluated in terms of scores focusing on motor output [ 23 ]. However, several lines of research reviewed elsewhere [ 24 , 25 , 26 , 27 ] have reported numerous non-motoric peculiarities of GTS patients, such as hypersensitivity to external stimuli [ 27 ] and general perceptual processing [ 28 ], abnormal sensorimotor interaction [ 29 , 30 ], and a dependence of symptoms on attention [ 31 , 32 , 33 ]. Moreover, the degree to which motor symptoms can be controlled [ 34 ] has been reported to form the basis of cognitive–behavioral interventions, and an increased tendency to create habits has been observed [ 35 , 36 , 37 ].…”
Section: Quo Vadis?mentioning
confidence: 99%
“…Due to its particularly notable motor symptoms, GTS has long been viewed and classified as a movement disorder, and treatment efficacy is indeed usually evaluated in terms of scores focusing on motor output [ 23 ]. However, several lines of research reviewed elsewhere [ 24 , 25 , 26 , 27 ] have reported numerous non-motoric peculiarities of GTS patients, such as hypersensitivity to external stimuli [ 27 ] and general perceptual processing [ 28 ], abnormal sensorimotor interaction [ 29 , 30 ], and a dependence of symptoms on attention [ 31 , 32 , 33 ]. Moreover, the degree to which motor symptoms can be controlled [ 34 ] has been reported to form the basis of cognitive–behavioral interventions, and an increased tendency to create habits has been observed [ 35 , 36 , 37 ].…”
Section: Quo Vadis?mentioning
confidence: 99%
“… 8 In addition to clinical observations, experimental data also suggest that altered processing of noise may indeed be evident in Tourette syndrome. 8 For instance, reduced sensory and sensorimotor gating in Tourette syndrome 9 is expected to lead to increased sensorimotor noise. Also, some data imply that in patients with Tourette syndrome tics are (mis-)interpreted as relevant action-related information (i.e.…”
Section: Introductionmentioning
confidence: 98%
“…Based on such clinical considerations, the ‘neural noise account of Tourette syndrome’ has recently been put forward. 8 This account suggests that the processing of neural noise and adaptation of the signal-to-noise ratio during information processing may be central to understand the nature of Tourette syndrome. 8 In addition to clinical observations, experimental data also suggest that altered processing of noise may indeed be evident in Tourette syndrome.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations